Respuesta :
Denote by [tex]X_{(n)}[/tex] the maximum order statistic, with [tex]X_{(n)}=\max\{X_1,\ldots,X_n\}[/tex], and similarly denote by [tex]X_{(1)}[/tex] the minimum order statistic. Then the CDF for [tex]X_{(n)}[/tex] is
[tex]F_{X_{(n)}}(x)=\mathbb P(X_{(n)}\le x)[/tex]
In order for there to be some [tex]x[/tex] that exceeds the value of [tex]X_{(n)}[/tex], it must be true that [tex]x[/tex] exceeds the value of all the [tex]X_i[/tex], so the above is equivalent to the joint probability
[tex]F_{X_{(n)}}(x)=\mathbb P(X_1\le x,\ldots,X_n\le x)[/tex]
and since the [tex]X_i[/tex] are i.i.d., we have
[tex]F_{X_{(n)}}(x)=\mathbb P(X_1\le x)\cdots\mathbb P(X_n\le x)=\mathbb P(X_1\le x)^n[/tex]
[tex]\implies F_{X_{(n)}}(x)=F_X(x)^n[/tex]
where [tex]X\sim\mathrm{Unif}(0,1)[/tex]. We have
[tex]F_X(x)=\begin{cases}0&\text{for }x<0\\x&\text{for }0\le x\le1\\1&\text{for }x>1\end{cases}[/tex]
and so
[tex]F_{X_{(n)}}(x)=\begin{cases}0&\text{for }x<0\\x^n&\text{for }0\le x\le1\\1&\text{for }x>1\end{cases}[/tex]
[tex]\implies f_{X_{(n)}}(x)=\begin{cases}nx^{n-1}&\text{for }0<x<1\\0&\text{otherwise}\end{cases}[/tex]
[tex]\implies\mathbb E[X_{(n)}]=\displaystyle\int_0^1xnx^{n-1}\,\mathrm dx=n\int_0^1x^n\,\mathrm dx=\frac n{n+1}[/tex]
Using similar reasoning, we can find the CDF for [tex]X_{(1)}[/tex]. We have
[tex]F_{X_{(1)}}(x)=\mathbb P(X_{(1)}\le x)=1-\mathbb P(X_{(1)}>x)[/tex]
[tex]F_{X_{(1)}}(x)=1-\mathbb P(X_1>x,\ldots,X_n>x)=1-\mathbb P(X_1>x)^n[/tex]
[tex]F_{X_{(1)}}(x)=1-(1-\mathbb P(X\le x))^n=1-(1-F_X(x))^n[/tex]
[tex]\implies F_{X_{(1)}}(x)=\begin{cases}0&\text{for }x<0\\1-(1-x)^n&\text{for }0\le x\le1\\1&\text{for }x>1\end{cases}[/tex]
[tex]\implies f_{X_{(1)}}(x)=\begin{cases}n(1-x)^{n-1}&\text{for }0<x<1\\0&\text{otherwise}\end{cases}[/tex]
[tex]\implies\mathbb E[X_{(1)}]=\displaystyle\int_0^1xn(1-x)^{n-1}\,\mathrm dx=\frac1{n+1}[/tex]
[tex]F_{X_{(n)}}(x)=\mathbb P(X_{(n)}\le x)[/tex]
In order for there to be some [tex]x[/tex] that exceeds the value of [tex]X_{(n)}[/tex], it must be true that [tex]x[/tex] exceeds the value of all the [tex]X_i[/tex], so the above is equivalent to the joint probability
[tex]F_{X_{(n)}}(x)=\mathbb P(X_1\le x,\ldots,X_n\le x)[/tex]
and since the [tex]X_i[/tex] are i.i.d., we have
[tex]F_{X_{(n)}}(x)=\mathbb P(X_1\le x)\cdots\mathbb P(X_n\le x)=\mathbb P(X_1\le x)^n[/tex]
[tex]\implies F_{X_{(n)}}(x)=F_X(x)^n[/tex]
where [tex]X\sim\mathrm{Unif}(0,1)[/tex]. We have
[tex]F_X(x)=\begin{cases}0&\text{for }x<0\\x&\text{for }0\le x\le1\\1&\text{for }x>1\end{cases}[/tex]
and so
[tex]F_{X_{(n)}}(x)=\begin{cases}0&\text{for }x<0\\x^n&\text{for }0\le x\le1\\1&\text{for }x>1\end{cases}[/tex]
[tex]\implies f_{X_{(n)}}(x)=\begin{cases}nx^{n-1}&\text{for }0<x<1\\0&\text{otherwise}\end{cases}[/tex]
[tex]\implies\mathbb E[X_{(n)}]=\displaystyle\int_0^1xnx^{n-1}\,\mathrm dx=n\int_0^1x^n\,\mathrm dx=\frac n{n+1}[/tex]
Using similar reasoning, we can find the CDF for [tex]X_{(1)}[/tex]. We have
[tex]F_{X_{(1)}}(x)=\mathbb P(X_{(1)}\le x)=1-\mathbb P(X_{(1)}>x)[/tex]
[tex]F_{X_{(1)}}(x)=1-\mathbb P(X_1>x,\ldots,X_n>x)=1-\mathbb P(X_1>x)^n[/tex]
[tex]F_{X_{(1)}}(x)=1-(1-\mathbb P(X\le x))^n=1-(1-F_X(x))^n[/tex]
[tex]\implies F_{X_{(1)}}(x)=\begin{cases}0&\text{for }x<0\\1-(1-x)^n&\text{for }0\le x\le1\\1&\text{for }x>1\end{cases}[/tex]
[tex]\implies f_{X_{(1)}}(x)=\begin{cases}n(1-x)^{n-1}&\text{for }0<x<1\\0&\text{otherwise}\end{cases}[/tex]
[tex]\implies\mathbb E[X_{(1)}]=\displaystyle\int_0^1xn(1-x)^{n-1}\,\mathrm dx=\frac1{n+1}[/tex]